A new species of the genus Achaemenothrombium (Acari: Achaemenothrombiidae) from Iran - Saboori, Alireza; Wohltmann, Andreas; Hakimitabar, Masoud; Shirvani, Asghar (Zootaxa, 2013)
Achaemenothrombium dariusi Saboori, Wohltmann & Hakimitabar sp. nov. (Acari, Prostigmata: Trombidioidea) is described and illustrated from larvae ectoparasitic on Euxoa fallax (Eversmann) (Lepidoptera: Noctuidae) from Sirch and Cheshmeh Bondar, Kerman province, Iran. It is the third species of this genus, which is recorded only from Iran. The status of this small family is discussed and a key to species of Achaemenothrombium (larvae) is presented.